Cyber and face to face bullying; who crosses over? - Ahmed, E; Braithwaite, V; Shin, H (My University, 2016)
A total of 3956 children aged 12–13 years who completed the Longitudinal Study of Australian Children (LSAC Wave 5) were studied about their experiences of traditional face-to-face bullying and cyberbullying in the last month. In terms of prevalence, sixty percent of the sample had been involved in traditional bullying as the victim and/or the offender whereas eight percent had been involved in cyberbullying as victim and/or offender. The vast majority (95 %) of those involved in cyberbullying were also involved in traditional bullying. Children involved in both traditional bullying and cyberbullying were compared with those involved in only traditional bullying. Boys were more likely to be involved in both types of bullying than girls. Children with friends involved in delinquent activities and who did not have trustworthy and supportive friends were more likely to bully both traditionally and in cyberspace. Computer proficiency and use did not differentiate children who had crossed over from those who had not, although computer use for socializing purposes had some predictive value in identifying those children who crossed over. The study reflects the value of school interventions for children as they approach adolescence, covering both traditional bullying and cyberbullying, and targeting social relationships in order to teach children how to manage them safely and intelligently.
Keywords: Actvities -- ICT use; Child Development -- Social; Child Development -- Behaviour; Childhood and child development; Actvities; Child Development; ICT use; Social; Behaviour; Childhood and child development